The Algorithm of Development the World Ocean Mining of the Industry During the Global Crisis - Nyrkov, Anatoliy; Budnik, Vladislav; Sokolov, Sergei; Chernyi, Sergei (IOP conference series. Materials Science and Engineering, 2016)
In the article reviewed extraction effect of hydrocarbons on the general country's developing, under the impact of economical, demographical and technological factors, as well as it's future role in the world energy balance. Also adduced facts which designate offshore and deep water production of unconventional and conventional hydrocarbons including mining of marine mineral resources as perspective area of development in the future, despite all the difficulties of this sector. In the article considered the state and prospects of the Russian continental shelf, in consideration of its geographical location and its all existing problems.